Superporous Poly(ethylene glycol) Diacrylate Cryogel with a Defined Elastic Modulus for Prostate Cancer Cell Research. Issue 29 (30th May 2016) - Göppert, Bettina; Sollich, Thomas; Abaffy, Paul; Cecilia, Angelica; Heckmann, Jan; Neeb, Antje; Bäcker, Anne; Baumbach, Tilo; Gruhl, Friederike J.; Cato, Andrew C. B.
Abstract : The physical and mechanical properties of the tumor microenvironment are crucial for the growth, differentiation and migration of cancer cells. However, such microenvironment is not found in the geometric constraints of 2D cell culture systems used in many cancer studies. Prostate cancer research, in particular, suffers from the lack of suitable in vitro models. Here a 3D superporous scaffold is described with thick pore walls in a mechanically stable and robust architecture to support prostate tumor growth. This scaffold is generated from the cryogelation of poly(ethylene glycol) diacrylate to produce a defined elastic modulus for prostate tumor growth. Lymph node carcinoma of the prostate (LNCaP) cells show a linear growth over 21 d as multicellular tumor spheroids in such a scaffold with points of attachments to the walls of the scaffold. These LNCaP cells respond to the growth promoting effects of androgens and demonstrate a characteristic cytoplasmic‐nuclear translocation of the androgen receptor and androgen‐dependent gene expression. Compared to 2D cell culture, the expression or androgen response of prostate cancer specific genes is greatly enhanced in the LNCaP cells in this system. This scaffold is therefore a powerful tool for prostate cancer studies with unique advantages over 2D cell culture systems. Abstract : Superporous poly(ethylene glycol) diacrylate cryogels mimicking the stiffness of malignant prostate tissues have been engineered for studies of prostate cancer cell growth and function. Cells grow in an anchorage‐dependent manner in this scaffold for three weeks and respond to androgen and antiandrogen treatment. Compared to 2D cell culture system, androgen‐dependent prostate target gene expression is highly regulated in this system.